How are changes in exposure to job demands and job resources related to burnout and engagement? A longitudinal study among Chinese nurses and police officers. (3rd April 2017) - Hu, Qiao; Schaufeli, Wilmar B.; Taris, Toon W.
Abstract: This study used a person‐centered approach to examine the across‐time relationships between job demands and job resources on the one hand and employee well‐being (burnout and work engagement) on the other. On the basis of the job demands–resources model and conservation of resources (COR) theory, increases in demands and decreases in resources across time were expected to result in unfavorable changes in well‐being across time. The results of a 2‐wave study among 172 nurses and 273 police officers showed several common patterns across both samples: (a) participants who experienced an increase of demands showed a significant increase in burnout, whereas participants who reported having low resources at both measurement times also showed a significant increase in burnout; (b) participants who experienced decreasing resources reported a significant increase in burnout and a significant decrease in engagement; (c) participants who were exposed to chronic low job resources in a highly demanding environment showed a significant increase in burnout; and (d) participants who were exposed to decreased job resources in a highly demanding environment showed a significant increase in burnout.